Electrochemical and photoluminescence response of laser-induced graphene/electrodeposited ZnO composites - N. F. Santos (Nature Portfolio, 2021)
Abstract The inherent scalability, low production cost and mechanical flexibility of laser-induced graphene (LIG) combined with its high electrical conductivity, hierarchical porosity and large surface area are appealing characteristics for many applications. Still, other materials can be combined with LIG to provide added functionalities and enhanced performance. This work exploits the most adequate electrodeposition parameters to produce LIG/ZnO nanocomposites. Low-temperature pulsed electrodeposition allowed the conformal and controlled deposition of ZnO rods deep inside the LIG pores whilst maintaining its inherent porosity, which constitute fundamental advances regarding other methods for LIG/ZnO composite production. Compared to bare LIG, the composites more than doubled electrode capacitance up to 1.41 mF cm−2 in 1 M KCl, while maintaining long-term cycle stability, low ohmic losses and swift electron transfer. The composites also display a luminescence band peaked at the orange/red spectral region, with the main excitation maxima at ~ 3.33 eV matching the expected for the ZnO bandgap at room temperature. A pronounced sub-bandgap tail of states with an onset absorption near 3.07 eV indicates a high amount of defect states, namely surface-related defects. This work shows that these environmentally sustainable multifunctional nanocomposites are valid alternatives for supercapacitors, electrochemical/optical biosensors and photocatalytic/photoelectrochemical devices.